Integrative Taxonomy of Southeast Asian Snail-Eating Turtles (Geoemydidae: Malayemys) Reveals a New Species and Mitochondrial Introgression - Ihlow, Flora; Vamberger, Melita; Flecks, Morris; Hartmann, Timo; Cota, Michael; Makchai, Sunchai; Meewattana, Pratheep; Dawson, Jeffrey E.; Kheng, Long; Rödder, Dennis; Fritz, Uwe (PLOS ONE, 2016)
Based on an integrative taxonomic approach, we examine the differentiation of Southeast Asian snail-eating turtles using information from 1863 bp of mitochondrial DNA, 12 microsatellite loci, morphology and a correlative species distribution model. Our analyses reveal three genetically distinct groups with limited mitochondrial introgression in one group. All three groups exhibit distinct nuclear gene pools and distinct morphology. Two of these groups correspond to the previously recognized species Malayemys macrocephala (Chao Phraya Basin) and M. subtrijuga (Lower Mekong Basin). The third and genetically most divergent group from the Khorat Basin represents a previously unrecognized species, which is described herein. Although Malayemys are extensively traded and used for religious release, only few studied turtles appear to be translocated by humans. Historic fluctuations in potential distributions were assessed using species distribution models (SDMs). The Last Glacial Maximum (LGM) projection of the predictive SDMs suggests two distinct glacial distribution ranges, implying that the divergence of M. macrocephala and M. subtrijuga occurred in allopatry and was triggered by Pleistocene climate fluctuations. Only the projection derived from the global circulation model MIROC reveals a distinct third glacial distribution range for the newly discovered Malayemys species.